Colorectal cancer patients under the age of 50 experience delays in primary care leading to emergency diagnoses: a population‐based study. (6th August 2019) - Arhi, C. S.; Ziprin, P.; Bottle, A.; Burns, E. M.; Aylin, P.; Darzi, A.
Abstract: Aim: The incidence of colorectal cancer in the under 50s is increasing. In this national population‐based study we aim to show that missed opportunities for diagnosis in primary care are leading to referral delays and emergency diagnoses in young patients. Method: We compared the interval before diagnosis, presenting symptom(s) and the odds ratio (OR) of an emergency diagnosis for those under the age of 50 with older patients sourced from the cancer registry with linkage to a national database of primary‐care records. Results: The study included 7315 patients, of whom 508 (6.9%) were aged under 50 years, 1168 (16.0%) were aged 50–59, 2294 (31.4%) were aged 60–69 and 3345 (45.7%) were aged 70–79 years. Young patients were more likely to present with abdominal pain and via an emergency, and had the lowest percentage of early stage cancer. They experienced a longer interval between referral and diagnosis (12.5 days) than those aged 60–69, reflecting the higher proportion of referrals via the nonurgent pathway (33.3%). The OR of an emergency diagnosis did not differ with age if a red‐flag symptom was noted at presentation, but increased significantly for young patients if the symptom was nonspecific. Conclusion: Young patients present to primary care with symptoms outside the national referral guidelines, increasing the likelihood of an emergency diagnosis.